Implementation of Article 32 of the Occupational Health and Safety Law in Municipalities of Metropolitan Lima - Vásquez Sánchez, José Ronald (2024)
International and national studies, such as those conducted in Garagoa (Colombia) and Lima (Peru), reveal that many municipalities have deficiencies in the implementation of the Occupational Health and Safety Management System (SG-SST), with low compliance levels attributed to the lack of risk monitoring and control measures, as well as associated costs. Therefore, this research aimed to evaluate the level of implementation of the Occupational Health and Safety Law in 20 district municipalities of Metropolitan Lima by verifying compliance with Article 32 of the Occupational Health and Safety Law. Additionally, it was found that the main barriers are the lack of monitoring, risk control, and associated costs. Greater attention and resources are needed to improve the organizational culture focused on preventing occupational accidents and diseases. It is concluded that the level of implementation of the Occupational Health and Safety Law in the district municipalities of Lima is low, with Pucusana and Lurín being exceptions with high compliance.